Creativity as a driver to Resilience in Cities.: The more creative the more resilient - Ondiviela García, José Antonio; Arvilla Gras, Ester Nicole; Moya Tudela, Paloma (Street Art & Urban Creativity, 2025)
The OECD defines urban resilience as a city’s ability to prepare for, absorb, and recover from adverse events, which are increasingly frequent due to human activity. We propose a direct relationship between resilience and creativity, where innovation is key to improving preparedness, reducing risks, and accelerating recovery. Based on the analysis of 175 cities from the Global Observatory of Attractive Cities for Talent and other sources, we developed creativity and resilience indices considering factors such as innovation, technology, culture, and risk preparedness. The study shows that the most creative cities are also the most resilient, as their innovative capacity enables effective solutions to challenges like natural disasters or economic crises, thereby fostering more adaptable and prepared urban environments.